2008
DOI: 10.1016/j.visres.2008.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Page mode reading with simulated scotomas: Oculo-motor patterns

Abstract: This study investigated the relationship between reading speed and oculo-motor parameters when normally sighted observers had to read single sentences with an artificial macular scotoma. Using multiple regression analysis, our main result shows that two significant predictors, number of saccades per sentence followed by average fixation duration, account for 94% of reading speed variance: reading speed decreases when number of saccades and fixation duration increase. The number of letters per forward saccade (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 38 publications
2
19
2
Order By: Relevance
“…In this study we found a comparable increase in fixation duration, but this failed to reach significance. Our results for fixation duration conflict with other studies that have used artificial scotomas with different tasks, including reading 30 and visual search tasks in highly regular search arrays 6, 10 . These tasks did not use a natural images but instead resolution-dependent stimuli.…”
Section: Discussioncontrasting
confidence: 99%
“…In this study we found a comparable increase in fixation duration, but this failed to reach significance. Our results for fixation duration conflict with other studies that have used artificial scotomas with different tasks, including reading 30 and visual search tasks in highly regular search arrays 6, 10 . These tasks did not use a natural images but instead resolution-dependent stimuli.…”
Section: Discussioncontrasting
confidence: 99%
“…Some recent reviews show the difficulty of providing a clear-cut understanding of crowding (Levi, 2008;Strasburger, Rentschler, & Jüttner, 2011). Crowding has also been invoked to account for reading deficits either in amblyopia (Levi, Song, & Pelli, 2007), in low vision (Wallace, Chiu, Nandy, & Tjan, 2013;Wallace, Chung, & Tjan, 2017), or in developmental dyslexia (Martelli, Filippo, Spinelli, & Zoccolotti, 2009) although this remains a controversial issue both in low vision (Bernard, Scherlen, & Castet, 2007;Calabrèse et al, 2010;Chung, 2004;Scherlen, Bernard, Calabrèse, & Castet, 2008) and dyslexia (Doron, Manassi, Herzog, & Ahissar, 2015;Ramus & Ahissar, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In gaze-contingent paradigms, the gaze location is monitored with an eyetracker and is then used to manipulate the visual information the observer is currently looking at. In one variant of such gaze-contingent paradigms, the moving mask technique (Rayner & Bertera, 1979), foveal information is degraded in order to investigate scene and object perception (Henderson, McClure, Pierce, & Schrock, 1997;Larson & Loschky, 2009;van Diepen, Ruelens, & d'Ydewalle, 1999), eye movement patterns in visual search (Bertera, 1988;Bertera & Rayner, 2000;Cornelissen, Bruin, & Kooijman, 2005) and reading (Fine & Rubin, 1999;Scherlen, Bernard, Calabrese, & Castet, 2008), and highlevel cognitive functioning such as visual context learning (Geringswald, Baumgartner, & Pollmann, 2012) when the observer is faced with a central scotoma.…”
Section: Introductionmentioning
confidence: 99%